Digital Transformation in the Correctional System Towards Effective Rehabilitation and Social Reintegration - Umi Enggarsasi; Nur Khalimatus Sa’diyah (International Journal of Law Reconstruction, 2025)
Digital transformation has emerged as a strategic response to longstanding problems in Indonesia’s correctional system, including overcrowding, high recidivism, and limited resources. Beyond administrative modernization, digitalization is increasingly viewed as a pathway toward a more humane and rehabilitative penal paradigm. This article examines how digital transformation contributes to rehabilitation and social reintegration of inmates in Indonesia. Using a qualitative juridical-empirical method, the study combines normative analysis of laws and human rights principles with empirical data drawn from policy reports, academic studies, and correctional practices. The findings highlight three key contributions of digitalization. First, rehabilitation efforts are strengthened through online learning platforms, digital vocational training, and virtual counseling programs that expand access to inmate development. Second, transparency and accountability are enhanced by integrated databases and complaint systems that reduce maladministration and increase public trust. Third, reintegration opportunities improve through digital entrepreneurship initiatives and technology-based connections with the labor market. These results suggest that digital transformation can be a vital instrument for realizing the rehabilitative mandate of Law Number 22 of 2022 and advancing restorative justice. Properly integrated into correctional policy, digitalization not only increases efficiency but also promotes a correctional system that is more just, inclusive, and socially sustainable.